A study of cortical and brainstem mechanisms of diffuse noxious inhibitory controls in anaesthetised normal and neuropathic rats. (6th October 2019) - Patel, Ryan; Dickenson, Anthony H.
Abstract: Diffuse noxious inhibitory controls (DNIC) are a mechanism of endogenous descending pain modulation and are deficient in a large proportion of chronic pain patients. However, the pathways involved remain only partially determined with several cortical and brainstem structures implicated. This study examined the role of the dorsal reticular nucleus (DRt) and infralimbic (ILC) region of the medial prefrontal cortex in DNIC. In vivo electrophysiology was performed to record from dorsal horn lamina V/VI wide dynamic range neurones with left hind paw receptive fields in anaesthetised sham‐operated and L5/L6 spinal nerve‐ligated (SNL) rats. Evoked neuronal responses were quantified in the presence and absence of a conditioning stimulus (left ear clamp). In sham rats, DNIC were reproducibly recruited by a heterotopically applied conditioning stimulus, an effect that was absent in neuropathic rats. Intra‐DRt naloxone had no effect on spinal neuronal responses to dynamic brush, punctate mechanical, evaporative cooling and heat stimuli in sham and SNL rats. In addition, intra‐DRt naloxone blocked DNIC in sham rats, but had no effect in SNL rats. Intra‐ILC lidocaine had no effect on spinal neuronal responses to dynamic brush, punctate mechanical, evaporative cooling and heat stimuli in sham and SNL rats. However, differential effects were observed in relation to the expression of DNIC; intra‐ILC lidocaine blocked activation of DNIC in sham rats but restored DNIC in SNL rats. These data suggest that the ILC is not directly involved in mediating DNIC but can modulate its activation and that DRt involvement in DNIC requires opioidergic signalling. Abstract : Neuropathic rats exhibit deficits in endogenous pain modulation as shown by a loss of diffuse noxious inhibitory controls (DNIC). In sham rats, the expression of DNIC requires opioidergic signalling in the dorsal reticular nucleus. In addition, the infralimbic cortex exerts bidirectional control of DNIC depending on pain state revealing novel pathophysiological mechanisms.